2012
DOI: 10.1186/1471-2369-13-145
|View full text |Cite
|
Sign up to set email alerts
|

Outpatient red blood cell transfusion payments among patients on chronic dialysis

Abstract: BackgroundPayments for red blood cell (RBC) transfusions are separate from US Medicare bundled payments for dialysis-related services and medications. Our objective was to examine the economic burden for payers when chronic dialysis patients receive outpatient RBC transfusions.MethodsUsing Truven Health MarketScan® data (1/1/02-10/31/10) in this retrospective micro-costing economic analysis, we analyzed data from chronic dialysis patients who underwent at least 1 outpatient RBC transfusion who had at least 6 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 17 publications
(15 reference statements)
0
12
0
Order By: Relevance
“…Using previously published [ 5 , 8 ] methods, we searched Medicare claims for outpatient transfusions and related services, including transfusion-related adverse events. No attempt was made to determine the specific indication for transfusion.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using previously published [ 5 , 8 ] methods, we searched Medicare claims for outpatient transfusions and related services, including transfusion-related adverse events. No attempt was made to determine the specific indication for transfusion.…”
Section: Methodsmentioning
confidence: 99%
“…These services included pre- and post-transfusion screening (antibody, chemistry, hematology, immunology) within 3 days before and after the transfusion, and acquisition and administration of blood products and storage. We also identified transfusion-related adverse events, including febrile non-hemolytic reaction, hemolytic reaction, air embolism, phlebitis, hyperkalemia, allergic reaction, congestive heart failure (CHF), transfusion-related lung injury, and transfusion related circulatory overload [ 8 ], within 3 days of the transfusion and delayed hemolytic reaction within 45 days. CHF hospitalizations were included as adverse events only for patients with no other CHF-related episodes in the 6 months before the transfusion.…”
Section: Methodsmentioning
confidence: 99%
“…The Clinformatics™ DataMart database, a product of OptumInsight Life Sciences, Inc. (Eden Prairie, MN), consists of a single, large insurance healthcare plan that includes more than 53 million unique members spanning over 12 years. The Truven MarketScan ® Commercial Claims and Encounter Database is constructed from privately insured paid medical and prescription drug claims for approximately 30 million employees and their dependents (in 2010) [ 14 ]. The MarketScan Medicare Supplemental Database contains the healthcare experience of individuals with Medicare supplemental insurance paid by employers for approximately 3.42 million retirees (in 2010) [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…The Truven MarketScan ® Commercial Claims and Encounter Database is constructed from privately insured paid medical and prescription drug claims for approximately 30 million employees and their dependents (in 2010) [ 14 ]. The MarketScan Medicare Supplemental Database contains the healthcare experience of individuals with Medicare supplemental insurance paid by employers for approximately 3.42 million retirees (in 2010) [ 14 ]. The Humana database consists of the entire fully-insured commercial and Medicare members belonging to the Humana health plan.…”
Section: Methodsmentioning
confidence: 99%
“…In previous work, we showed that while infrequent, payments for RBC transfusion complications were very high when complications occurred; mean payments for complications ranged from $213 (SD = $168) for delayed hemolytic transfusion reactions to $19,466 (SD = $15,424) for congestive heart failure [21]. Additionally, RBC transfusions can result in sensitization to human leukocyte antigen (HLA), which reduces the opportunity for future kidney transplantation [29].…”
Section: Discussionmentioning
confidence: 99%